TINJAUAN DEKONSTRUKTIF ATAS KONSEP OTORITAS KHALED M. ABOU EL-FADL - Abdulloh Hanif (UIN Sunan Kalijaga Yogyakarta, 2020)
This article discusses a deconstructive review of the concept of authority of Khaled M. Abou el-Fadl. The phenomenon of authoritarianism is now the most troubling phenomenon for the development of contemporary Islamic thought. This phenomenon not only describes a rigid and undeveloped tradition of Islamic thought, but also has an impact on immoderate socio-religious behavior. Khaled M. Abou el-Fadl described this phenomenon as a consequence of human representation of Islamic authority. In terms of representation by authoritative humans, humans are often treated authoritatively and out of the substance of Islamic authority itself. This authoritarian attitude in treating the authoritative foundation of Islam is what Khaled calls authoritarianism. It can reside in humans and manipulate meanings into interpretations which often only serve the interests of some people. Through the deconstruction method, authoritarianism does not only appear as an arbitrary attitude towards authority, but also shows a conceptual network that indirectly shifts the construction of authority itself. Khaled, besides showing an attitude of